Rites of Spring - Peter Nicholls (CoSMO, 2023)
This paper reads in tandem two major poems: Giacomo Leopardi’s canzone Alla Primavera, o delle favole antiche (“To Spring, or on the ancient myths”) and T. S. Eliot’s The Waste Land. Composed almost exactly one hundred years apart, the two works display some curious affinities in the “rites of Spring” they ironically enact. Eliot never expressed interest in Leopardi, but both poems meditate on classicism, romanticism, and myth, and both are produced in a period of personal and national turmoil for their writers. Read together they might be taken to dramatize the passage between the “modern” work of 1822 and the “modernist” one of 1922, each legible (as Eliot wrote of Igor Stravinsky’s Rite of Spring and James Frazer’s The Golden Bough) either “as a collection of entertaining myths, or as a revelation of that vanished mind of which our mind is a continuation.”